United Kingdom : Technical Assistance Report-Assessment of HMRC's Tax Gap Analysis. (IMF Staff Country Reports; Country Report ;, 2013)
This Technical Assistance Report discusses assessment of HMRC's (Her Majesty's Revenue and Customs) Tax Gap Analysis program in United Kingdom, and provides advice and guidance on further improving it. The HMRC's tax gap analysis program is comprehensive in tax coverage, and effectively addresses its multiple dimensions. The report addresses three aspects of the program: (1) the models and methodologies employed; (2) the approach to disseminating the results; and (3) the use of the results in supporting compliance activities, evaluating tax revenue performance across taxes and the effectiveness of HMRC. The report also raises some areas of possible further research.